A Contamination Sensor Based on an Array of Microfibers with Nanoscale-Structured Film. (1st July 2014) - Zhou, Guorui; Yuan, Xiaodong; Lü, Hai-Bing; Zhou, Hai; Wang, Haijun; Wang, Hongbin; Miao, Xinxiang
Abstract : A contamination sensor based on an array of microfibers with nanoscale-structured film using evanescent field is proposed and demonstrated theoretically and experimentally. When the molecular contaminants deposit on the nanoscale-structured film, the refractive index of the film will change and the additional loss will be produced due to the disturbance of evanescent field. The possibility of the sensor is demonstrated theoretically by using three-dimensional finite-difference time domain (3D-FDTD). The corresponding experiments have also been carried out in order to demonstrate the theoretical results. Microfibers are fabricated by using hydrogen-oxygen flame-heated scanning fiber drawing method and the nanoscale-structured film coated on the surface of microfibers is deposited by using dip coating process. Then an array of microfibers is assembled to demonstrate the feasibility of the device. The experimental results show that contaminants detection with the device can agree well with the results measured by the laser-scattering particle counter, which demonstrates the feasibility of the new type of contaminant sensor. The device can be used to monitor contaminants on-line in the high-power laser system.